Geochemical and Microbial Signatures of Siboglinid Tubeworm Habitats at an Active Mud Volcano in the Canadian Beaufort Sea - Lee, Dong-Hun; Kim, Jung-Hyun; Lee, Yung Mi; Kim, Ji-Hoon; Jin, Young Keun; Paull, Charles; Ryu, Jong-Sik; Shin, Kyung-Hoon (Frontiers in Marine Science, 2021)
During the ARA08C expedition in 2017, sediment push cores were collected at an active mud volcano (420 m water depth) in the Canadian Beaufort Sea from two visually-discriminative siboglinid tubeworm (ST) habitats that were colonized densely and less densely (ST1 and ST2, respectively). In this study, we investigated the biogeochemical and microbial community characteristics at ST1 by analyzing the geochemical properties, microbial lipids, and nucleic acid signatures, and comparing them with the data previously reported from ST2. The two ST sites showed distinct differences in vertical geochemical gradients (methane, sulfate, dissolved inorganic carbon (DIC), total organic carbon, and total sulfur), with a higher methane flux recorded at ST1 (0.05 mmol cm-2 y-1) than at ST2 (0.01 mmol cm-2 y-1). Notably, the δ13C values of DIC were more depleted at ST1 than at ST2, resulting in a higher proportion of DIC derived from the anaerobic oxidation of methane (AOM) at ST1 than at ST2. Moreover, both the ST1 and ST2 sites revealed the dominance of AOM-related lipid biomarkers (especially sn-2-hydroxyarchaeol), showing highly 13C-depleted values. The 16S rRNA analyses showed the presence of AOM-related archaea, predominantly anaerobic methanotrophic archaea (ANME)-3 at ST1 and ST2. Our results suggest that AOM-related byproducts (sulfide and DIC) potentially derived from ANME-3 were more abundant at ST1 than at ST2. This variation was attributed to the intensity and persistence of ascending methane. Therefore, our study suggests that AOM-derived byproducts are possibly an essential energy source for tubeworms during chemosynthetic metabolism, shaping different colony types on the seafloor.